Reflection Article: Psychological Effects on Women Victims of Sexual Violence (Cuidado y Ocupación Humana, 2025)
This article reflects on sexual violence and the psychological effects, persuasions in victims of sexual abuse and nursing theories, on the theoretical basis of the different authors that highlight some conceptual implications of the comprehension component. Sexual violence is a very common phenomenon in today's societies, which generates irreparable damage in the people who suffer it, causing feelings of sadness, anxiety, depression, guilt, shame, suicide attempts and also leaves significant consequences in the interpersonal and family relationships, which limit the full development of the life cycle of these women who are victims of this type of violence. This topic review article has the general objective of determining the psychological effects on women victims of sexual violence and how it affects their general well-being, however, through this article it is intended to inform about the psychological damage generated by sexual violence in women. The alternative is proposed as a perspective psychological effects on women victims of sexual violence in mental health approaches.
Keywords: Sexual violence; post traumatic stress; psychological effects; depression; anxiety; low self-esteem